2013
DOI: 10.1002/bjs.9035
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of perioperative steroids on ischaemia–reperfusion injury and surgical stress response in patients undergoing liver resection

Abstract: Perioperative steroids have a favourable impact on postoperative outcomes after liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 55 publications
2
51
0
2
Order By: Relevance
“…The results of the present study with regard to postoperative IL-6 are consistent with recent meta-analyses of randomized controlled trials of preoperative corticosteroids in colorectal surgery, liver surgery and esophagectomy [21][22][23][24]41]. In addition, the present metaanalysis reports a significant reduction in IL-6 on postoperative days 2, 3 and 5 in those patients given preoperative corticosteroids.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study with regard to postoperative IL-6 are consistent with recent meta-analyses of randomized controlled trials of preoperative corticosteroids in colorectal surgery, liver surgery and esophagectomy [21][22][23][24]41]. In addition, the present metaanalysis reports a significant reduction in IL-6 on postoperative days 2, 3 and 5 in those patients given preoperative corticosteroids.…”
Section: Discussionsupporting
confidence: 91%
“…16,17,19 Although procedure-specific dose-response studies are still required, the positive effects have been shown in biliary and hepatic surgery and colorectal procedures 16,19,29 and also in cardiac surgery regarding postoperative infection, duration of postoperative mechanical ventilation, hyperthermia, and LOS. 30,31 Before general recommendations for perioperative glucocorticoid administration can be made, obviously conclusive safety studies must be available.…”
Section: Discussionmentioning
confidence: 98%
“…30,31 Before general recommendations for perioperative glucocorticoid administration can be made, obviously conclusive safety studies must be available. So far, there seem to be no safety issues [15][16][17][18][19][29][30][31] related to a single preoperative dose of glucocorticoid including specific studies on wound healing. 32,33 The consequences of preoperative high-dose glucocorticoids for glucose homeostasis need further evaluation, but so far the transitory increased hyperglycemic response has not been related to increased postoperative complications 34 supported by the findings in this study-taking into account the limited number of patients in the subgroup of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Die ausgeschütteten Zytokine, Chemokine, Wachstumsfaktoren und Zelloberflächenantigene haben während der Gewebeschädigung eine kurze Halbwertszeit, können allerdings über eine Verstär-kung der Signalkaskade und Aktivierung anderer Immunzellen einen sich weiter verstärkenden Schaden hervorrufen, besonders wenn die initiale Noxe bestehen bleibt [20,21]. Experimentell konnte sich die Gabe von Kortikosteroiden positiv auf diese Effekte auswirken [22,23].…”
Section: Diskussionunclassified